Metallogenic mechanism of the Houge’zhuang gold deposit, Jiaodong, China: Evidence from fluid inclusion, in situ trace element, and sulfur isotope compositions - Chi, Naijie; Han, Zuozhen; Liu, Chuan’e; Zhang, Wei; Zhang, Yanhui; Shan, Wei; Li, Zengsheng; Li, Min; Wang, Xiufeng; Sun, Yuqin (Frontiers in Earth Science, 2022)
The Houge’zhuang gold deposit, located in the Penglai–Qixia gold belt of the Jiaodong peninsula, is a representative auriferous quartz vein-style deposit. Pyrite is the most common and main gold-bearing mineral and shows complex textures in the Houge’zhuang gold deposit. Study of ore-related pyrite is of great significance for understanding the metallogenesis of this deposit, especially the gold precipitation mechanism. The present study applied systematic microscopic observation, fluid inclusion analysis, electron microprobes,in situ LA-ICP-MS trace-element analysis, and in situ sulfur isotope analyses. Three types of fluid inclusions were identified, among which the ore-forming fluids exhibited medium–low salinity and temperature, with the fluid inclusions mainly comprising H2O and CO2. Three types of pyrites were identified: 1) Py0, characterized by low concentrations of As and Au and low δ34S values (5.51–6.86‰). 2) Py1, found in the gold-quartz-pyrite veins and homogeneous in chemical composition with no obvious zonal growth but with notably more gold and chalcopyrite inclusions. Py1 contained medium and uniform concentrations of As and was Au-rich, with δ34S values ranging from 7.13 to 7.89‰ (mean 7.44‰). 3) Py2 contained arsenic-bearing pyrite and was found in quartz-polymetallic sulfide veins, with distinct As enrichment and As-rich rims of pyrite and growth zoning. Consequently, the primary ore-forming fluids passed through some arsenic and δ34S-rich sedimentary rocks, such as the Jingshan, Fenzishan, and Penglai groups. With the occurrence of stable water-rock interaction, the extracted fluids were enriched for As and δ34S. Furthermore, Au was closely associated with As, visible gold grains tended to occur in association with Py1 at stage II, and invisible gold was related to the Au-As-rich Py2 of stage III. The As-bearing pyrites shared a close spatiotemporal relationship with gold, playing an important role in the formation and exploration of high-grade gold deposits.